Analysis and Experimental Investigation of A356 Aluminium Alloy Hybrid Composites Reinforced with Gr-FE3O4-B4C Nanoparticles Synthesised by Selective Laser Melting (SLM). (9th July 2022) - Anoop, J.; Suyamburajan, Vijay Ananth; Babu, P. Sekhar; Filketu, Sisay Addis
Abstract : Additive manufacturing techniques (AMTs) evolved quickly from simple prototype options to promising additive manufacturing techniques. The additive technologies, which include point-by-point material merging, full melting, and solidification of powder particles, provide potential unique braves and advantages with nanometal powders. In the fabrication of A356 aluminium alloy-based hybrid metal matrix nanocomposites, graphite (Gr), iron oxide (Fe3 O4 ), and boron carbide (B4 C) are used as nanoreinforcement. Famous AMTs like selective laser melting have created A356 hybrid nanocomposites (SLM). The ingot was made out of a cylindrical slot measuring 14 × 100 mm. The percentages 2%, 4%, and 6% are added to the reinforcements Gr, Fe3 O4, and B4 C. Microtensile and microhardness tests were used to determine the outcome of the reinforcement. Microtensile and microhardness parameters are assessed using microtensile test equipment and a Vickers hardness tester, with the specimen prepared in accordance with ASTM standards. A356 with 2, 4, and 6% reinforcing has a Vickers Hardness Number (VHN) of 144, 163, and 188, respectively. As the boron carbide reinforcement is increased, the load value of graphite and iron oxide (2, 4, and 6%) rises. The greatest ultimate tensile strengths are 260.10, 290.06, and 325.43 N/mm 2, respectively. The bonding structure of nanocomposites is assessed using an OM, and then, microtensile specimens are assessed using a SEM. As a result of the superior effect of the diverse reinforcements Gr, Fe3 O4, and B4C, more increased tensile and hardness qualities have been attained.